Common property, the Golden Age, and Empire in Acts 2:42-47 and 4:32-35 - Noble, Joshua (Library of New Testament studies, 2020)
Preface Acknowledgments Abbreviations -- 1. Introduction -- 2. The Golden Age Myth in Greek and Latin Sources -- 3. The Golden Age Myth in Jewish and Christian Sources -- 4. Preliminaries to a Golden Age Reading of the Acts Summaries -- 5. Reading Acts -- 2.42-47 and -- 4.32-35 as Golden Age Allusions -- 6. Conclusion -- Bibliography -- Index